The novel NADPH oxidase 4 inhibitor GLX351322 counteracts glucose intolerance in high-fat diet-treated C57BL/6 mice. (2nd November 2015) - Anvari, E.; Wikström, P.; Walum, E.; Welsh, N.
Abstract: In type 2 diabetes, it has been proposed that pancreatic beta-cell dysfunction is promoted by oxidative stress caused by NADPH oxidase (NOX) overactivity. Five different NOX enzymes (NOX1–5) have been characterized, among which NOX1 and NOX2 have been proposed to negatively affect beta-cells, but the putative role of NOX4 in type 2 diabetes-associated beta-cell dysfunction and glucose intolerance is largely unknown. Therefore, we presently investigated the importance of NOX4 for high-fat diet or HFD-induced glucose intolerance using male C57BL/6 mice using the new NOX4 inhibitor GLX351322, which has relative NOX4 selectivity over NOX2. In HFD-treated male C57BL/6 mice a two-week treatment with GLX351322 counteracted non-fasting hyperglycemia and impaired glucose tolerance. This effect occurred without any change in peripheral insulin sensitivity. To ascertain that NOX4 also plays a role for the function of human beta-cells, we observed that glucose- and sodium palmitate-induced insulin release from human islets in vitro was increased in response to NOX4 inhibitors. In long-term experiments (1–3 days), high-glucose-induced human islet cell reactive oxygen species (ROS) production and death were prevented by GLX351322. We propose that while short-term NOX4-generated ROS production is a physiological requirement for beta-cell function, persistent NOX4 activity, for example, during conditions of high-fat feeding, promotes ROS-mediated beta-cell dysfunction. Thus, selective NOX inhibition may be a therapeutic strategy in type 2 diabetes.